Collaborative Learning in Three British Adult Education Schemes - Moira Lee (Adult Education Research Conference, 2000)
This qualitative case study research is located in three British adult education schemes. The focus of the research is on the values of collaborative learning and the roles of facilitators and participants in collaborative learning communities.